2018
DOI: 10.1002/jper.17-0674
|View full text |Cite
|
Sign up to set email alerts
|

Memory T cell subsets in healthy gingiva and periodontitis tissues

Abstract: Our findings suggest that recirculating and gingiva-resident memory T cells could represent an important part of the immune surveillance network in the connective tissue, maintaining periodontal homeostasis. Imbalance of subgingival bacterial communities could damage gingival barrier allowing bacterial antigens to get access to the deeper connective tissue where they activate memory T cells leading to deleterious inflammation; a hallmark of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 48 publications
1
31
0
5
Order By: Relevance
“…The extension of CD69 expression seems to be a function of bacteria and antigens exposure. In agreement with findings by Mahanonda et al on periodontitis tissue specimens harvested from sites of extracted teeth, the present study also showed a higher number of CD69+ T cells in the epithelium and connective tissue collected during flap operation procedures . A positive correlation was also observed between number of CD69+ and CD103+ T cells and PD, but the immunohistochemical analysis failed to demonstrate a gradient of these cells from the gingival margin to the bottom of the periodontal pockets.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The extension of CD69 expression seems to be a function of bacteria and antigens exposure. In agreement with findings by Mahanonda et al on periodontitis tissue specimens harvested from sites of extracted teeth, the present study also showed a higher number of CD69+ T cells in the epithelium and connective tissue collected during flap operation procedures . A positive correlation was also observed between number of CD69+ and CD103+ T cells and PD, but the immunohistochemical analysis failed to demonstrate a gradient of these cells from the gingival margin to the bottom of the periodontal pockets.…”
Section: Discussionsupporting
confidence: 92%
“…Flow cytometry could be used to evaluate antigens co‐expression, but requires tissue fragmentation, thus losing information regarding cell localization (eg, intraepithelial or not). In this context, the study by Mahanonda et al demonstrated the presence of Trm cells in single cells suspension from periodontitis tissues of four patients but it did not distinguish between the epithelial or stromal localization . Novel approaches are now enabling precise spatial profiling of multiple antigens and could thus enable full characterization of these cells in future studies …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations